Shear-band affected zone revealed by magnetic domains in a ferromagnetic metallic glass - Shen, L. Q. (Nat Commun, 2018)
Plastic deformation of metallic glasses (MGs) has long been considered to be confined to nanoscale shear bands, but recently an affected zone around the shear band was found. Yet, due to technical limitations, the shear-band affected zone (SBAZ), which is critical for understanding shear banding and design of ductile MGs, has yet to be precisely identified. Here, by using magnetic domains as a probe with sufficiently high sensitivity and spatial resolution, we unveil the structure of SBAZs in detail. We demonstrate that shear banding is accompanied by a micrometer-scale SBAZ with a gradient in the strain field, and multiple shear bands interact through the superimposition of SBAZs. There also exists an ultra-long-range gradual elastic stress field extending hundreds of micrometers away from the shear band. Our findings provide a comprehensive picture on shear banding and are important for elucidating the micro-mechanisms of plastic deformation in glasses.